Short-term impacts of air temperature on hospitalizations for mental disorders in Lisbon - Almendra, Ricardo (2019)
Background: Individuals with mental disorders are often susceptible to the effects of extreme ambient temperatures. The aim of this study is to assess the short-term impacts of daily mean temperature on hospitalizations for mental disorders in the Lisbon Metropolitan Area, Portugal. Methods: To assess the short-term impacts of daily mean temperature on hospitalizations for mental disorders (2008–2014), a quasi-Poisson generalized additive model combined with a distributed lag non-linear model was applied. The model was adjusted for day of the week, air pollution, relative humidity, time and seasonality. Results: The number of hospital admissions for mental disorder during the study period was 30,139. Hospital admissions increase significantly with high temperatures on day of exposure, at lag 0–1 and at lag 0–2.Women are more vulnerable than men, and there was no difference between the age groups studied. Conclusions: The exposure to high temperatures should be considered a significant risk factor for mental disorders; therefore, patient management services may need to be strengthened when extreme high temperature alerts are given.